2007
DOI: 10.1002/bit.21611
|View full text |Cite
|
Sign up to set email alerts
|

The bactericidal effect of ultraviolet and visible light on Escherichia coli

Abstract: The bactericidal radiation dosages at specific wavelengths in the ultraviolet (UV)-visible spectrum are not well documented. Such information is important for the development of new monochromatic bactericidal devices to be operated at different wavelengths. In this study, radiation dosages required to cause mortality of an Escherichia coli strain, ATCC 25922, at various wavelengths between 250 and 532 nm in the UV and visible spectrum were determined. Radiation at 265 nm in the UV region was most efficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 14 publications
13
41
0
Order By: Relevance
“…Although the laser irradiation performed in the present study could kill the bacteria, the bactericidal effect (<2-log reduction of the CFU/mL in 30 min) was weaker than that of photo-irradiated proanthocyanidin. This finding agrees with a previous study, which showed that irradiation with UV or visible blue light could exert bactericidal action depending on the level of irradiation [21]. Even though treatment with proanthocyanidin or laser irradiation alone was not effective, the laser irradiation of the suspension containing proanthocyanidin could kill the bacteria very effectively.…”
Section: Discussionsupporting
confidence: 92%
“…Although the laser irradiation performed in the present study could kill the bacteria, the bactericidal effect (<2-log reduction of the CFU/mL in 30 min) was weaker than that of photo-irradiated proanthocyanidin. This finding agrees with a previous study, which showed that irradiation with UV or visible blue light could exert bactericidal action depending on the level of irradiation [21]. Even though treatment with proanthocyanidin or laser irradiation alone was not effective, the laser irradiation of the suspension containing proanthocyanidin could kill the bacteria very effectively.…”
Section: Discussionsupporting
confidence: 92%
“…For this it was first necessary to select and characterize adequate light conditions with view on practical relevance. It was reported that the spectral composition of the incident light is a critical determinant for the viability of biotechnological cultures exposed to direct illumination 21. Indirect effects, caused by a priori light exposure of the culture medium, will most probably exhibit the same, wavelength‐dependent variations, as different chemical groups will be differentially affected at a given wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…We note that ThT undergoes a spectral shift and intensity increase when highly concentrated or when spatially constricted, either by binding to amyloid fibrils or by viscosity [Maskevich et al, 2015, Sulatskaya et al, 2017. Our choice of filters aims at minimizing these effects and the damage that shorter wavelengths cause to E. coli [Vermeulen et al, 2008]. Cells were imaged in a custom-built flow-cell ( Fig.…”
Section: Fluorescence Microscopymentioning
confidence: 99%